Evaluation of mobile health applications using the RE-AIM model: systematic review and meta-analysis - Jorge, Emanuele Louise Gomes de Magalhães; Ferreira, Emily de Souza; Pereira, Michele Duarte; Mingote, Ana Luiza Paes; Silva, João Henrique Corrêa; Moreira, Tiago Ricardo; Cotta, Rosângela Minardi Mitre (Frontiers in Public Health, 2025)
BackgroundThe Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) model has been used as an instrument to determine the impact of the intervention on health in digital format. This study aims to evaluate, through a systematic review and meta-analysis, the dimensions of RE-AIM in interventions carried out by mobile health apps.MethodsThe systematic review and meta-analysis were conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and involved searching six databases - Medline/PubMed, Embase, CINAHL, Virtual Library in Health, and Cochrane Library. The review included randomized, cross-sectional, and cohort clinical trials assessing the prevalence of each RE-AIM dimension according to the duration of the intervention in days. The quality of the selected studies was evaluated using the Joanna Briggs Institute tool. The random effects meta-analysis method was used to explain the distribution of effects between the studies, by Stata® software (version 11.0) and publication bias was examined by visual inspection of graphs and Egger’s test.ResultsAfter analyzing the articles found in the databases, and respecting the PRISMA criteria, 21 studies were included, published between 2011 and 2023 in 11 countries. Improvements in health care and self-management were reported for various conditions. The result of the meta-analysis showed a prevalence of 67% (CI: 53–80) for the reach dimension, of 52% (CI: 32–72) for effectiveness, 70% (CI: 58–82) for adoption, 68% (CI: 57–79) for implementation and 64% (CI: 48–80) for maintenance.ConclusionThe RE-AIM dimensions are useful for assessing how digital health interventions have been implemented and reported in the literature. By highlighting the strengths and areas requiring improvement, the study provides important input for the future development of mobile health applications capable of achieving better clinical and health promotion outcomes.Systematic Review RegistrationPROSPERO. International Prospective Registry of Systematic Reviews. CRD42024556886.